The Prevalence and Intensity of Louse (Pthiraptera, Mallophaga) and Tick (Acarina,Ixodidae) Infestation of Birds in South African Grassland - Kopij, G.; Price, R.D. (Вестник зоологии, 2011)
A total of 270 birds represented by 12 species were examined for the presence of lice and ticks. Birds were collected in South African grasslands. Extensity of louse and tick infestation ranged from 10% to 80% and from 3% to 33% respectively. Average number of lice per host species ranged from 1 to 15, while average number of ticks per host species ranged from 1 to 5. Only single specimens (0.4%) were heavily parasited by lice and ticks respectively. Lice infested birds more often during the dry season, while ticks infested birds mainly during the rain season. В общей сложности 270 птиц 12 видов были обследованы на наличие пухоедов и клещей. Птицы были собраны на южноафриканских пастбищах. Экстенсивность зараженности пухоедами и клещами колеблется от 10% до 80% и от 3% до 33%, соответственно. Среднее количество пухоедов на вид-прокормитель колеблется от 1 до 15, а среднее число клещей на вид-прокормитель – от 1 до 5. Только единичные особи (0,4%) были сильно паразитированы пухоедами и клещами соответственно. Пухоеды заражали птиц чаще всего во время сухого сезона, в то время как клещи заражали птиц в основном во время сезона дождей.